ANÁLISE DO DISCURSO FUNDADOR DE TELÊMACO BORBA NO JORNAL O TIBAGI (1948-1964) - Vieira, Ana Flávia Braun (2015)
SUMMARY: Being Telemaco Borba – PR known as “the Klabin’s city”, this paper has as purpose the content analysis of the O Tibagi newspaper, owned by Horacio Klabin, in order to find what was the influence of the jornal in building the founding speech in this city. To this end, discussions were held about the political and power relations and its ability to estabilish a history; it were identified the elements of the oficial history of the city; finally, the content analysis was made in the anual anniversary editions of the weekly, between the years of 1948 and 1964, considering both the speeches of self-recerentiality, who built the place of the newspaper as enunciator of knowledge to the montealegrense society, such as outerrerefentiality, and its contribuition to the organization’s founding speech and the establishment of local offical history. From the analysis of theses sources it was concluded the the newspaper O Tibagi, through the dissemination of his speeches, as it silences over the past previous to the arrival or industrial, reached his readers with other senses, contributing in this way, with a new history to the place.